Scientific and pedagogical schools «System analysis in engineering and control» and its contribution to educational the process of universities - Yuriy S. Vasil’ev; Violetta N. Volkova; Vladimir N. Kozlov; Artem A. Efremov (Открытое образование (Москва))
In 2018, the 20th anniversary of the Scientific and Pedagogical School “System Analysis in Engineering and Control”, which unites scientists who developing the Theory of Systems and System Analysis in various universities in Russia, Ukraine, Norway, Poland, USA, Finland and other countries.The school considers itself to be a successor of: the school of the Moscow Energy Institute, in which Dr. of Technical Sciena, Professor F.E. Temnikov (1906-1993), created in 1970 the first in the country the department in the direction of the theory of systems and system studies, the Department of System Engineering$ and the school of the Leningrad Polytechnic Institute (now Peter the Great St. Petersburg Polytechnic University), which since 1973 at the Faculty of Technical Cybernetics Doctor of Technical Sciences, Professor, (later -Honored Scientist of the Russian Federation) A.A. Denisov (1934-2010) studied the generality of processes in systems of various physical nature and also proposed the theory of the information field and information, approach to analysis of system.In 1994, Dr. Tech. Professor, Honored Worker of the Higher School of the Russian Federation, VN Kozlov, renamed the Department of Technical Cybernetics headed by him, to the Depart-ment”System Analysis and Management” and opened a new direction of the same name for the preparation of bachelors and masters,and this is played a major role in the establishment of the Polytechnic University scientific and pedagogical school.Since 1998, on the basis of the Polytechnic University, a conference “System Analysis in Engineering and Control” has been held annually, which has become the basis for the formation of a school with the same name of unifying scientists from Russian and foreign universities and research institutes involved in the development the Theory of Systems and System Analysis as applied theory of systems..This article is characterized by the main results, which over the past 20 years, scientists, united by the school, made contribution to the development of Theory of Systems, System Analysis and other scientific directions.